Daun Jambu Biji (Psidium guajava L.) sebagai Antikanker Payudara - Dwitiyanti (Universitas Indonesia, 2015)
Guava leaves are used as a cytotoxic compound. Previous research has demonstrated that guava leaves contained 61.71% of quercetin and potential as an cytotoxic compound. The aim of this study was to determine the cytotoxic activity of 70% ethanol extract of guava leaves against T47D cancer cells. The method used was direct counting (viable cell count) to obtained the LC50 value. This study tested six concentrations of 70% ethanol extract of guava leaves that were 130.62; 67.98; 35.98; 18.43; 9.56 and 5 µg/ml. The LC50 value from the 70% ethanol extract of guava leaves was 27.54 µg/ml. The results suggested that the extract of guava leaves has cytotoxic activity against T47D cells.